Problems and Alternative Solutions for the Implementation of Islamic Education Learning during the Pandemic: A Literature Review - I'anatut Thoifah; Saeful Biantoro (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2021)
This study aims to analyze the problems in the implementation of PAI (Islamic Education) learning, based on the results of preliminary research that the highest percentage of problems in the implementation of PAI learning is 44.4% internet network disturbances. This study uses a qualitative approach to the type of literature review by collecting information and data from various literature (scientific articles) through the google scholar journal search database, researchers enter the boolean operators "AND" and "OR" to specify the search for data. While the results of this study obtained 9 articles that provide alternative solutions to network problems including 1) finding a place that allows strong access; 2) replacing the cellphone card that can access the network better, 3) tethering with other family members; 4) applying to use the principle of flexibility in deciding policies and finding learning solutions during the COVID-19 pandemic; 5) doing tasks manually (limited face-to-face); 6) using the facilities provided by the Ministry of Education, Culture, Research, and Technology in the form of learning programs on television (TVRI); 7) providing data packets; 8) prepare the material manually, students take it at school and do it at home. 9) looking for a place with free Wi-Fi with health protocols; 10) giving more time in collecting assignments with the collection system at school or at the teacher's house. Therefore, the implementation of education needs to be supported by policymakers to continue to provide the facilities needed in the implementation of online learning, one of which is access to a stable network as an effort to achieve effectiveness and achieve educational goals.